Unquenched Flavor in the Gauge/Gravity Correspondence - Carlos Núñez; Ángel Paredes; Alfonso V. Ramallo (Advances in High Energy Physics)
Within the AdS/CFT correspondence, we review the studies of field theories with a large number of adjoint and fundamental fields, in the Veneziano limit. We concentrate in set-ups where the fundamentals are introduced by a smeared set of D-branes. We make emphasis on the general ideas and then in subsequent chapters that can be read independently and describe particular considerations in various different models. Some new material is presented along the various sections.